Developing Interactive Quiz Media Based on Genially Application to Improve Students' Learning Motivation - Erni Kusrini Sitinjak; Lolyta Damora Simbolon; Golda Novatrasio Sauduran (Jurnal Penelitian Pendidikan IPA, 2025)
The minimal use of interactive learning media in the implementation of quizzes during learning causes a lack of enthusiasm and motivation for students to work on the given practice questions. This study aims to develop an interactive quiz using the genially application as a learning tool to improve the learning motivation of grade VI students at Public Elementary Schools in Paropo. The research method used is R&D (Research and Development) with the ADDIE model. Data were collected through interviews, observations, and questionnaires, then analyzed quantitatively and qualitatively. This study was validated by material experts and media experts. The results of the validation of material experts showed an average score of 87% and validation of media experts with an average of 90% and the quiz results obtained by students in the experimental class averaged 82.70 while the average quiz score of students in the control class was 60. From the aspect of student motivation in the category of students who are active in learning, an average of 83.3% has increased from the previous average of 33.3%. In the category of enthusiasm in learning, it increased to 82.2%. And the category of student interest in the implementation of learning after implementing the genially application became 88.3%.